The Probability of Transition to Entrepreneurship Revisited: Wealth, Education and Age - Mondragon-Velez, Camilo (2012)
This paper revisits the empirical relationship between the probability of transition to entrepreneurship and wealth. Given that wealth is correlated with both education and age, these observable characteristics cannot be treated as independent covariates in the estimation. Thus, I document the differences in the transition probability profile across age and education groups. The main result of this paper is that the estimated probability of transition to entrepreneurship is hump-shaped in wealth across cohorts defined by age and education. Therefore, the aggregate profile estimated by Hurst and Lusardi (J Polit Econ 112(2):319-347, 2004) is not representative at the micro level. In addition, this paper provides facts that evidence important differences between entrepreneurs and workers, as well as among entrepreneurs, across education and age.